Estudo da influência catalítica e de co-processamento na pirólise de óleo de cozinha residual - Sartori, Wyllian Winckler (2019)
Recent economic crises involving crude oil, as well as uncertainties about availability and concern for the environment have stimulated several countries to seek alternatives in fuel production. For example, Brazil instituted the National Biofuels Policy (RenovaBio) through the law n° 13,576/2017, which adopts the voluntary national commitment of actions to stimulate the production of biofuels, especially biokerosene (Biojet). Over this scenary, researches using waste biomasses as a renewable source to obtain higher value-added biofuels and chemicals have increased in recent years. Therefore, waste cooking oil (WCO) chosen as the promise source of biomass for this study due to its high availability, besides being a residue, that when not properly treated can become as a great environmental pollutant. By means the pyrolytic co-processing between WCO and cattle manure (CM), as well as the use of catalysts, this work has showed the conditions for the production of bio-oil hydrocarbon-enriched in the range of aviation fuels (C9-C16). Co-pyrolytic processing in the ratio 1:1 indicated a positive synergistic effect, especially with respect to the production of paraffinic, olefins and aromatic hydrocarbons, desirable for biokerosene. In the catalytic pyrolysis process, the molybdenum and cobalt (Mo-Co) catalysts supported in α-Al2O3, presented a better effectiveness, producing an acid-free bio-oil with a high concentration of paraffins, olefins and aromatics.